2021
DOI: 10.3390/su131810081
|View full text |Cite
|
Sign up to set email alerts
|

Island Tourism-Based Sustainable Development at a Crossroads: Facing the Challenges of the COVID-19 Pandemic

Abstract: Tourism is often seen as the ‘golden ticket’ for the development of many islands. The current COVID-19 pandemic, however, has ground global tourism to a halt. In particular, islands that depend heavily on tourist inflows—including mass-tourism islands, and small island developing states (SIDS)—have seen their revenues diminish significantly, and poverty rates increasing. Some alternative-tourism islands have fared better, as they have focused on providing personalized, nature-based experiences to mostly domest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…The maintenance of these travel bubbles can serve to sustain international tourism activities not only in the new normal but also in the events of potential crises. In the view of Figueroa and Rotarou [76], responsible governance, the management of natural resources and related tourism activities, addressing environmental issues, the diversification of products, and the elevation of innovative and personalized tourist experiences are key to ensuring resilience as a part of future health-and environment-related crises.…”
Section: Best Practices To Secure a Sustainable Futurementioning
confidence: 99%
“…The maintenance of these travel bubbles can serve to sustain international tourism activities not only in the new normal but also in the events of potential crises. In the view of Figueroa and Rotarou [76], responsible governance, the management of natural resources and related tourism activities, addressing environmental issues, the diversification of products, and the elevation of innovative and personalized tourist experiences are key to ensuring resilience as a part of future health-and environment-related crises.…”
Section: Best Practices To Secure a Sustainable Futurementioning
confidence: 99%
“…Therefore, it is likely that a relatively high percentage of respondents were travelling with low or no confidence. For this segment of travellers, measures such as "COVID-19-free tourist travel corridors" [33] or COVID-19-free islands [34] could be a way to restore travellers' confidence. On the other hand, around 49% of the respondents had no fears about COVID-19 when travelling by public means of transport (Figure 3b), whereas up to around 48% of the respondents sometimes did not feel protected.…”
Section: Perception Of the Risk Of Covid-19 Infection When Travellingmentioning
confidence: 99%
“…Zhao et al [28] found that there are recreational and cultural ecosystem service values for island tourism. Eugenio and Rotarou [29] found that the key issues of island tourism are the governance and management of natural resources and tourism activities, the impacts of climate change, the diversification of economies, and the promotion of innovative and personalized tourist experiences.…”
Section: The Initial List Of Sustainable Island Tourism Evaluation Cr...mentioning
confidence: 99%